Faculty support and students’ academic motivation - Raboca, Horia M.; Carbunarean, Florin (Frontiers in Education, 2024)
This study investigates the relationship between students' perceptions regarding faculty support and their overall level of academic motivation. Other aspects like types of academic motivation (intrinsic and extrinsic motivation or amotivation) grounded in self-determination theory are also addressed. The findings indicate that there is a significant positive correlation between faculty support and the overall level of student's academic motivation. At the same time, the results show that both psychological and functional support, as indicators of faculty support, have influence on different types of academic motivation. In this sense, faculty support has a moderate positive influence on student'sintrinsic academic motivation, respectively a moderate negative influence on academic amotivation. These results can be of interest for faculty decision makers. In other words, any educational policy or strategy adopted by faculty-level decision makers designed to help students improving their academic performance must include elements and activities related to providing support (at social, psychological, and functional level).